Pengaruh Struktur Modal, Pertumbuhan Perusahaan Dan Kinerja Keuangan Perusahaan Terhadap Nilai Perusahaan Sub Sektor Makanan Dan Minuman Di Bursa Efek Indonesia - Mega Fortuna Ariani; Evaliati Amaniyah (Jurnal Kajian Ilmu Manajemen (JKIM), 2021)
The Company value is one of the most important things in a company. The value of the company is reflected by the stock price which shows the public's assessment of the company's financial performance. The value of the company is able to increase the welfare of shareholders if the share price increases because the value of the company shows the level of welfare of the shareholders. The purpose of this study is to determine the effect of capital structure, company growth and company  financial performance on company  value in food and beverage sub-sector companies listed on the Indonesia Stock Exchange in 2015 - 2019. This study uses a quantitative approach and  statistical tools like multiple regression analysis in conducting hypothesis testing. Partially, the results of this study show that company  value in food and beverage sub-sector companies listed on the Indonesia Stock Exchange in 2015 - 2019 is affected by capital structure and financial company performance, while company growth does not affect company value . Simultaneously, the results of this study show that capital structure, company growth, and company financial performance effect on the value of company in food and beverage sub-sector companies on the Indonesia Stock Exchange. The coefficient of determination (R2) in this study is 74.6%, this indicates that capital structure, company growth and financial performance company can explain  company value about 74.6%, while 25.4% is explained by other variables. outside of this study.